(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
ABSTRACT The purpose of this study is to find out how the responsiveness of sim service officers carried out by the Makassar City Police, it can be used a type of quantitative research with a quantitative descriptive type of research, while the number of informants in this study amounted to 50 people. Data collection techniques use questionnaires in the form of checklists, interviews, and documentation. The results showed that in general, the level of responsiveness of driver’s license service officers at the Makassar City Police, which was measured using indicators proposed by Zeithaml which consisted of indicators of the ability to respond to the community, perform services quickly, at the right time, and carry out services according to procedures and incoming payments, in the category of both seen from the results of the analysis using the SPSS application with a significant level of 0.000 <0.05. Keywords : Responsiveness, Service